THE THOUGHTS OF A MESCID BOOK ON THE PERIOD OF THE AHLÂTSAHLAR IN ERCIS - Yusuf ÇETİN (Fırat University, 2021)
Ahlatşahlar, settled around Lake Van, and ruled between 1100 and 1208, is one of the first Turkish principalities established in Anatolia. Although historical sources give detailed information about the reconstruction activities of Ahlatşahlar period, which is one of the prominent principalities due to the fertility of the land where it was established and being located at the crossroads of trade routes, not much has survived except for a few building remains. In Erciş, one of the important centers of the principality, 585 H, which we detected in Kasımbağı District, draws attention with the stamps on a mosque inscription dated 1189-1190. The fact that this inscription is the only mosque inscription whose history is known with certainty among the mosques built during the Ahlatşahlar period is important in terms of the architectural inventory of the Ahlatşahlar period as well as the inventory of the early period Anatolian Turkish mosque architecture.